1996
DOI: 10.1597/1545-1569_1996_033_0312_tdcbtp_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Comparison between the Palatal Forms in Complete Unilateral Cleft Lip and Palate with and without Hotz Plate from Cheiloplasty to Palatoplasty

Abstract: The palatal forms in 20 infants with a complete unilateral cleft lip, and palate (12 with a Hotz plate and 8 without, selected at random) were studied from birth until 18 months of age. Using techniques developed previously, the degree of curvature In the palate and the magnitude of migration of the maxillary segments were measured three-dimensionally. Furthermore, using a newly developed method to approximate a set of the points on the alveolar ridge to a circle in a plane, the form of the alveolar arch was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 9 publications
2
30
1
3
Order By: Relevance
“…The changes found in the maxillary arches of patients who received early pre-surgical orthopaedic treatment were evaluated. It was observed that the anterior dimension of the cleft (APL-APS) showed a statistically significant reduction in all patients, which is in accordance with other authors (16). Between time points A and B, the reduction was significant in those patients who used modified PNAM due to the addition of acrylic and trimming of the plates (17)(18)(19).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The changes found in the maxillary arches of patients who received early pre-surgical orthopaedic treatment were evaluated. It was observed that the anterior dimension of the cleft (APL-APS) showed a statistically significant reduction in all patients, which is in accordance with other authors (16). Between time points A and B, the reduction was significant in those patients who used modified PNAM due to the addition of acrylic and trimming of the plates (17)(18)(19).…”
Section: Discussionsupporting
confidence: 89%
“…This slight undesired effect might be due to the soft material of the plate. These results do not agree with Mishima et al (16), where the same measurement increased. Baek and Son concluded that the width of the mid-part of the larger and smaller segments decreased from the initial visit until one month before the cheiloplasty during treatment with the plate and, after surgery, it was stable (22).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Every effort to diminish bias was made. Sampling bias was minimized, because the patients in the included trials originated from university departments (61)(62)(63)(64)(65) or academic hospitals and CP centers (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)66). Bias concerning eligibility and quality of the original studies was tackled by having two authors independently assessed the articles, and any disagreement was resolved by consulting the first author until a final consensus was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The dentoalveolar changes in the maxillary arch were measured by means of special 3D measurement equipment (3D Tristation Ò ; 3D Reflex Microscope Ò ) in two series of studies (43,55,(62)(63)(64)(65) at four time points: at 1-2 weeks (T1), at 6 months (T2), at 18-19.5 months (T3), and at 48 months (T4). The maxillary arch depth was examined by measuring the depth perpendicular from the top of the interdental papilla between the central incisors (I) to the intertuberosity point distance (TT¢).…”
Section: Dentoalveolar Treatment Outcomesmentioning
confidence: 99%